Study of distribution of thermal fluxes in a plate of aluminum with nanoporous aluminum oxide by means of thermal imaging measurements - H. T. Dinh; N. V. Lushpa; K. V. Chernyakova; I. A. Vrublevsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The paper presents the results of studies of heat fluxes in a printed circuit board made of aluminum with nanoporous anodic alumina, generated by linear heat source. It is established that in this case the shape of the cone of the heat pipe with the beginning from a point heating source on the surface was characterized by expansion towards the back side of the aluminum base. This effect leads to a decrease in the thermal resistance of the printed circuit board.